2020
DOI: 10.1186/s12905-020-00922-w
|View full text |Cite
|
Sign up to set email alerts
|

Intention to quit water pipe smoking among Iranian women: a qualitative directed content analysis

Abstract: Background: Water-pipe smoking is the most common type of tobacco used among Iranian women. The aim of this study was to explain women's perceptions of their intention for quitting water-pipe smoking based on the theory of planned behavior. Methods: The study was a qualitative content analysis which was carried out over 4 months in 2016 in Tehran-Iran. The participants were 26 women ages 18 to 45-years-old who smoked water-pipe and were selected through snowball sampling. The study was performed in hookah cafe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Some participants have been going to traditional teahouses for over 4 years, showing that it is difficult for them to quit smoking hookah and leave that friendly atmosphere. The results of this research support the findings of other researches that social experience (16,20), positive attitude (17), feeling relaxed (8), leisure time (21,22), and difficulty to quit (23) are the main reasons for pushing adults to hookah smoking. Ansari et al, in a study conducted in Sistan and Baluchestan Province, found that 53% of these people smoked hookahs in groups, and 12.6% of hookah smokers used it every other day (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some participants have been going to traditional teahouses for over 4 years, showing that it is difficult for them to quit smoking hookah and leave that friendly atmosphere. The results of this research support the findings of other researches that social experience (16,20), positive attitude (17), feeling relaxed (8), leisure time (21,22), and difficulty to quit (23) are the main reasons for pushing adults to hookah smoking. Ansari et al, in a study conducted in Sistan and Baluchestan Province, found that 53% of these people smoked hookahs in groups, and 12.6% of hookah smokers used it every other day (24).…”
Section: Discussionsupporting
confidence: 89%
“…Barnett et al found that relaxation and social experience were the main reasons for hookah smoking; moreover, the dangers of hookah smoking were misunderstood by the participants (16). Sabzmakan et al assessed hookah smoking among Iranian women and figured out that positive perspective, social pressure, and false beliefs about hookah smoking pushed them to smoke (17). Mohammadpoorasl et al found that the obscenity of hookah smoking is less than cigarettes, and because of this, adults prefer to smoke hookah (18).…”
Section: Introductionmentioning
confidence: 99%
“…The association between attitude and hookah smoking behavior is clear [ 23 ], as in a qualitative study by Sabzmakan et al (2020), a positive attitude and misconceptions regarding hookah usage were the primary determinants of the intention not to quit [ 26 ]. In addition, studies by Abedini et al (2014) and Elias et al (2017) verified the correlation between misunderstandings regarding hookah use and hookah smoking behavior [33–34].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of studies on the factors affecting hookah use and the impact of a theory-based educational program [ 22 ]. In a study by Sabzmakan et al, a positive attitude and misconceptions and regarding hookah usage were the primary determinants of the intention not to quit [ 26 ]. In addition, in other studies verified the correlation between misunderstandings regarding hookah use and hookah smoking behavior [33–34].Based on research findings, educational programs designed Based on Theory of Planned Behaviour to prevent and regulate tobacco, cigarettes, and hookah are beneficial [ 22 , 23 , 29 – 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used the theory of planned behavior as our construct to summarize future intentions as a predictor of behavior change. The central construct in the theory of planned behavior suggests that intentions are the best predictors of behavior change (Gollwitzer, 1999;Institute of Medicine, 2002;Sabzmakan et al, 2020).…”
Section: Methodsmentioning
confidence: 99%